THE EFFECT OF HEALTHY EXERCISE ON BLOOD PRESSURE IN HYPERTENSION PATIENTS IN THE GYMNASTICS GROUP IN ROWOKANGKUNG DISTRICT - Izzaturrohmah Senna; Sasmiyanto; M. Ali Hamid (Penerbit Hellow Pustaka, 2024)
This study aims to determine the effect of healthy exercise on blood pressure in hypertension sufferers in the Rowokangkung District Gymnastics Group. This research used a non-probability sampling method (saturated sample) and was conducted in January 2024. These findings show that healthy exercise can effectively reduce blood pressure in hypertensive patients. The study also revealed that women are more likely to suffer from high blood pressure than men, especially postmenopausal. Factors such as age, education, and occupation (eg civil servant) also influence the risk of hypertension. The research highlights the benefits of exercise in managing hypertension, including improving physical and mental health, reducing stress, and slowing the aging process. This research provides valuable insight for the community and becomes a reference for further research in the field of nursing and hypertension management. The population in this study consisted of 33 hypertensive patients consisting of 13 men and 20 women who were members of the Gymnastics Group in Rowokangkung District. The sample includes the entire population of 33 people, because this research uses a non-probability sampling method (saturated sample). In this study, bivariate analysis was used with paired tests (t tests) and normality using skewness and kurtosis and hypothesis testing.